Recovery of Bioactive Constituents from Olive Leaf Pruning Waste of Five Different Cultivars: A Comparison of Green Extraction Techniques to Maximize Health Benefits - Hamid Mushtaq; Simona Piccolella; Jose A. Mendiola; Lidia Montero; Elena Ibáñez; Severina Pacifico (Foods)
Sustainable agro-waste revaluation is critical to enhance the profitability and environmental footprint of the olive oil industry. Herein, the valorization of olive leaf pruning waste from five cultivars (‘Caiazzana’, ‘Carolea’, ‘Itrana’, ‘Leccino’, and ‘Frantoio’) employed green extraction methods to recover compounds with potential health benefits. Sequential ultrasound-assisted maceration (UAM) in n-hexane and ethanol was compared with a compressed fluid extraction strategy consisting of supercritical fluid extraction (SFE) and pressurized liquid extraction (PLE) for their efficiency in recovering distinct classes of bioactives. Chemical profiling by UHPLC-HR-MS/MS (ultra-high-performance liquid chromatography high-resolution tandem mass spectrometry) and GC-MS (gas chromatography mass spectrometry) showed that UAM-EtOH effectively extracted polyphenols (especially luteolin derivatives) and triterpenes (notably maslinic acid), while PLE yielded the highest amount of secoiridoids (e.g., secologanoside). PLE extracts showed better antiradical activities, putatively due to a higher content of flavonoids, secoiridoids, and HCA derivatives than UAM-EtOH ones, as these latter also contained 20–40% (cultivar-dependent) of triterpenes. SFE extracts with a higher concentration of fatty acids and triterpenes showed moderate antioxidant activities but very high AChE inhibition. This study highlights the importance of selecting appropriate extraction methodologies based on the target bioactive compounds and underscores the potential of olive leaf extracts for sustainable bio-products.